Composites with Excellent Insulation and High Adaptability for Lightweight Envelopes - Liang Guo; Wenbin Tong; Yexin Xu; Hong Ye (Energies, 2018)
Lightweight insulation materials are widely used in lightweight buildings, cold-chain vehicles and containers. A kind of insulation composite, which can combine the super insulation of state-of-the-art insulation materials or structures and the machinability or adaptability of traditional insulation materials, was proposed. The composite consists of two components, i.e., polyurethane (PU) foam as the base material and vacuum insulation panel (VIP) or silica aerogel as the core material. The core material is in plate shape and covered with the base material on all sides. The thermal conductivity of the core material is nearly one order lower than that of the base material. The effective thermal conductivity of the insulation composite was explored by simulation. Simulation results show that the effective thermal conductivity of the composite increases with the increase of the thermal conductivity of the core material. The effective thermal conductivities of the composites decrease with the increase of the cross-section area of the core material perpendicular to heat flow direction and the thicknesses of the core material parallel with heat flow direction. These rules can be elucidated by a series-parallel mode thermal resistance network method, which was verified by the measured results. For composite with a VIP as the core material, when the cross-section area and thickness of the VIP are respectively larger than 60% and 21% of the composite, the composite’s effective thermal conductivity can be 50% or less than that of the base material. Simulated heat loss of the envelope adopting the insulation composites with VIP as the core material is nearly a half of that of the envelope adopting traditional insulation materials.